The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s11356-020-10753-9
|View full text |Cite
|
Sign up to set email alerts
|

A coupled UV photolysis-biodegradation process for the treatment of decabrominated diphenyl ethers in an aerobic novel bioslurry reactor

Abstract: The commercial flame retardant is an emerging contaminant (EC) commonly found in soils and sediments. A coupled UVphotolysis-biodegradation process was used to decompose decabromodiphenyl ether (BDE-209) in clay slurries. A novel bioslurry bioreactor (NBB) was employed in which BDE-209 degradation was maximized by the simultaneous application of LED UVA irradiation and biodegradation by a mixed bacterial culture. The rate of BDE-209 degradation decreased in the order: coupled UV photolysis-biodegradation (1.31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Polyphenolic and flavonoid compounds have well‐known beneficial properties to human health, such as α‐glucosidase inhibition, antioxidant activities, and anti‐inflammatory activity (Im et al., 2016; Kashchenko & Olennikov, 2020), which is mainly attributed to their chemical structures containing multiple hydroxyl substituents on an aromatic ring (Dulic et al., 2019). It is reported that microbial biodegradation may lead to the cleavage and hydroxylation of the aromatic ring (Chang et al., 2021), and some microorganisms could use substrates containing aromatic rings as nutrients (Ni et al., 2013; Vera‐Cabrera et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenolic and flavonoid compounds have well‐known beneficial properties to human health, such as α‐glucosidase inhibition, antioxidant activities, and anti‐inflammatory activity (Im et al., 2016; Kashchenko & Olennikov, 2020), which is mainly attributed to their chemical structures containing multiple hydroxyl substituents on an aromatic ring (Dulic et al., 2019). It is reported that microbial biodegradation may lead to the cleavage and hydroxylation of the aromatic ring (Chang et al., 2021), and some microorganisms could use substrates containing aromatic rings as nutrients (Ni et al., 2013; Vera‐Cabrera et al., 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The content changes of flavonoids and polyphenols during fermentation may be due to their continuous degradation, convertation, and synthesis during the growth and metabolic processes of microorganisms ( 36 ). For instance, it is reported that microbial degradation may cause the cleavage and hydroxylation of the aromatic ring in flavonoids and polyphenols ( 37 ). Their precipitation or oxidation during the fermentation process may also lead to decrease of these compounds ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
“…The first-order rate constants (k) for BDE-209 degradation containing TiO 2 -Yi-Li immobilized chitosan beads in the present study decreased in the order TiO 2 -Yi-Li immobilized chitosan beads (k = 0.166, 1/day) > Yi-Li immobilized chitosan beads (k = 0.132, 1/day). Previously, the rates of BDE-209 degradation in a clay slurry system have been ranked for an aerobic novel bioslurry reactor in the order: coupled UV photolysis-biodegradation (k = 0.0131, 1/day) > UV photolysis alone (k = 0.011, 1/day) > biodegradation alone (k = 0.01, 1/day) [10]. The slowest rate constant for BDE-209 degradation was found to be 0.0054 1/day when the Yi-Li bacterial-mixed culture was added, and the degradation carried out in the dark [23].…”
Section: Discussion 41 Advantages Of Tio 2 -Yi-li Immobilized Chitosa...mentioning
confidence: 99%
“…and Stenotrophomonas spp., have the ability to biodegrade PBDEs [6][7][8]. However, microbial bioremediation requires a longer treatment time compared with chemical oxidation remediation or a modified bioremediation process [9,10]. To improve the efficiency of PBDEs biodegradation, one possibility is to combine various eco-friendly physical/chemical/biological processes [10][11][12].…”
Section: Introductionmentioning
confidence: 99%